The Influence Of The Mixture Feed Kayambang (Salvinia Molesta D. S Mitchell) With Different Compositions To The Growth Of Sangkuriang Catfish (Clariass Spp) Enlargement Age (Grower) - Siti Diana Fathia; Soesy Asiah Susilawaty; Rini Solihat (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2020)
Experimental research aims to determine the influence of mixed feed S. Molesta with different composition on the growth of Clarias Sp. The treatment carried out on this study included 3 different compositions of the S. Molesta flour is treatment A composition of the addition of S. Molesta is different from 20.62 grams (to reach A protein 30%), B treatment of S. Molesta composition given at 13.34 grams (to achieve protein 40%), and the treatment C composition of S. Molesta of 6, 05 gram (to reach protein 50%) and control (feeding factory F782). From the results of the study showed that the influence of artificial feed S. Molesta is best at treatment A and the lowest at the treatment of C. Based on research conducted the average weight increase Clarias SP is in the treatment of A 0.781 grams and the most significant increase in the length of the average in treatment A (30% protein) increased by 0.433 cm. Friedman test results show there is a difference in weight and length Clarias sp which is given the treatment of feed A, B and C and feed the plant (P > 0.05). The conclusion of the study was the influence of the feed mix S. Molesta to Growth Clarias SP age enlargement.